(untitled) (CIPEEX, 2025)
The objective of the research project is to compare the effects of a psychomotor intervention program based on the organization of therapeutic settings in cycles, with the effects obtained by a conventional psychomotor intervention program based on an activity circuit on the motor development and participation of children with Autism Spectrum Disorder (ASD). This is a randomized controlled clinical trial with a blinded evaluator that will involve 30 children diagnosed with ASD. The participants will be evaluated one week before the intervention, one week and one month after the end of the interventions, using the Childhood Autism Rating Scale, the Autism Classification System: Social Communication, the Motor Development Assessment Battery, and the Participation and Environment Measure for Children and Youth. The interventions will be held twice a week, carried out over four consecutive weeks, totaling eight sessions of 45 minutes each. The experimental group will carry out the psychomotor intervention program based on the organization of Therapeutic Setting in cycles. The control group will carry out the psychomotor intervention program. In both interventions, the psychomotor structures of balance, tone, body awareness, laterality, spatial organization, gross motor skills, and fine motor skills will be focused on in the proposed activities. The results will be statistically analyzed assuming a significance level of p≤0.05.